Enhancing Listening Comprehension through Testing: a Case Study - Aziz, Othman H. (Journal of University of Human Development, 2015)
Listening comprehension is one of the important skills in foreign language learning, however, there has been relatively little research in this field. For that matter, testing listening skill has not had a long history either. Currently the situation is different and the listening test has been given sufficient weight in language testing and assessment. Almost all standardized and proficiency English language tests throughout the world include listening component (e.g. TEFOL, ILETS, various Cambridge Exams). Certain universities have even included a listening component in their entrance examination (e.g. in Japan); while other educational institutions have made an English proficiency certificate (which has a listening component) a graduation requirement (e.g. HCT in UAE). This study aims at investigating the effect of ’pre-test preparation’ on test achievement. The subjects were a group of 3rd year university students on a B.A. degree programme in English, in Kurdistan region, Iraq. The project extended over a period of three months; during which the students were being prepared to sit for two proficiency (standardized) listening tests, namely Cambridge Preliminary (known as PET). Results of the first test, as expected, were rather unsatisfactory. The students were made aware of their mistakes through analysis of their test results. After a period of two months the students were put through another listening test of the same level of proficiency to find out if their familiarity with the test processes and procedures would affect their test achievement. The results showed remarkable improvement. It is hoped that this study and the suggestions that are made, would be of benefit for teachers and test-takers alike, in tackling some issues related to listening comprehension.